2010
DOI: 10.2146/ajhp090670
|View full text |Cite
|
Sign up to set email alerts
|

Impact of telepharmacy in a multihospital health system

Abstract: The implementation of telepharmacy services in a multihospital health system expanded hours of service, improved the speed of processing of physician medication orders, and increased clinical pharmacy services and cost avoidance. Surveys of health care staff found that telepharmacy services were well received.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(55 citation statements)
references
References 34 publications
0
53
0
Order By: Relevance
“…Previous studies have focused on describing telepharmacy activities in a small number of hospitals 5,8,[13][14][15][16][17][18][19][20][21] or in a single hospital. 22,23 Studies have reported the impact of telepharmacy by tracking medication error rates, 4 by describing pharmaceutical care activities focused on drug-related problems, 5 by evaluating number of orders reviewed, modified, discontinued, and voided by remote pharmacists, 9 by describing the 24-h pharmacy staffing coverage given, 15 or…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have focused on describing telepharmacy activities in a small number of hospitals 5,8,[13][14][15][16][17][18][19][20][21] or in a single hospital. 22,23 Studies have reported the impact of telepharmacy by tracking medication error rates, 4 by describing pharmaceutical care activities focused on drug-related problems, 5 by evaluating number of orders reviewed, modified, discontinued, and voided by remote pharmacists, 9 by describing the 24-h pharmacy staffing coverage given, 15 or…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, after telepharmacy services were implemented in five hospitals within an integrated health system, nurses' global satisfaction with pharmacist availability for unit consultations was significantly improved. These studies also showed an increase in clinical interventions, which the authors estimated to result in cost savings …”
Section: Implementation and Evaluationmentioning
confidence: 94%
“…Although this study was not powered to measure patient outcomes, improved outcomes from the provider side will likely improve patient outcomes in turn . Overall, although telehealth appears to reduce workplace burnout, research in this area is ongoing, and these outcomes should be considered for inclusion in a CMM telehealth evaluation plan …”
Section: Implementation and Evaluationmentioning
confidence: 99%
“…12 Although it may be impractical for most rural hospitals to implement many of the costly, labor-intensive processes used at urban hospitals, telemedicine can offer a practical, cost-effective alternative. 5,17,18 …”
Section: Introductionmentioning
confidence: 99%